(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
The author has issued a correction to the publication Caledonia Romana by Robert Stuart (1845). Stuart’s publication claims that Agricola’s camp near Cleghorn is on the right of the road to Edinburgh and that only one part of its ramparts remains visible. However, according to Rankin, this camp is on the left of the road and is mostly in tact. He relates a description of the current state of the camps at Cleghorn and Castledykes with regerence to General Roy’s plans from 1753 an 1764. Rankin then finishes with a brief overview of General Roy’s early life in Carluke. Meetings minutes for 14 March 1853 are appended.